THE PROCESS OF FIXING PAINTS OF MIXED TECHNIQUE, CONTRAST, BLEACHING AND DARKENING ON NATURAL ECOLOGICAL ORGANIC FABRIC IN ARTS AND CRAFTS, PAINTING FABRIC IN BATIK TECHNIQUE IN AUTOCLAVES A AT HOME (American Journal of Research in Humanities and Social Sciences, 2023)
This article discusses ways to fix the dye on a natural ecological organic fabric using the batik technique. The types and characteristics of steaming in a mixed technique of contrast of bleaching and darkening are considered.